Characteristics of Beef Jerky Added by Fresh Red Ginger (Zingiber officinale var. Rubrum) as A Seasoning - Maulida Nugrahaning Gusti, Zahra; Suryati, Tuti; Wulandari, Zakiah (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Jerky is a processed meat product that can have rancidity due to storage. Adding fresh red ginger as a spices can inhibit the growth of bacteria, increasing antioxidant activity, and potentially increasing tenderness. This study aims to examine the characteristics of beef jerky added by fresh red ginger (Zingiber officinale var. Rubrum) as a seasoning. This study used the addition of fresh red ginger with proportion 0%, 12,5% and 25% from meet weight. Beef was sliced with a thickness of 5 mm then was marinated with spices for 12 hours. Marinated beef was dried using oven at 60°C for 3 hours and 70°C for 5 hours. The results showed that the addition of fresh red ginger to beef jerky was able to increase pH, aw, moisture content, DPPH inhibitory activity, and antioxidant capacity, as well as reduce hardness, TBARS value and TPC numbers. Salmonella sp., Escherichia coli and Staphylococcus aureus bacteria were not detected in all treatments and storage. The red ginger concentration of 12.5% in both raw and cooked beef jerky was preferred by the panelists. Beef jerky with the addition of 25% fresh red ginger showed the best results for testing the physicochemical, sensory, microbiological, and antioxidant activity properties.